A FORMAÇÃO DOCENTE EM NÍVEL MÉDIO NO BRASIL: FUNDAMENTOS HISTÓRICOS, MATRIZES POLÍTICAS E PROJETOS PEDAGÓGICOS EM DISPUTA. UM ESTUDO CRÍTICO A PARTIR DO PPP DO COLÉGIO ESTADUAL VISCONDE DE GUARAPUAVA EM GUARAPUAVA-PR - Leite, Francielly Cristina Wisnievski Trelha (2018)
This research studies the Training Course for Teachers at the intermediate level, Normal modality, of the State College Visconde de Guarapuava. The course is a possibility of starting a professional teaching career that has been discussed since the 1920s. Currently, it is organized by LDB 9394/96 which admits as a minimum training for the exercise of teaching in early childhood and 5 (five) first years of elementary school, the one offered at the middle level, in the normal modality. The research problem consists in investigating whether the current model of the course allows a polytechnical formation to the students, that is, an integral formation of the man: an omnilateral formation that brings in its aspects of human emancipation, reading of the world, participation, collectivity and political and social responsibility. In this sense, it was necessary to reflect how the World Bank policies directly influence the reconfiguration of the State and the redefinition of educational policies. We also show the documents guiding the course, especially the PPP of the school, as well as the curricular matrix of the course. This research was carried out through analysis of the Federal and State Educational Legislation, documents of the State Secretariat of Education of Paraná, Political Pedagogical Project, and bibliographic analysis based on the following authors: Dermeval Saviani (2009), Maria Ciavatta (2014), Antonio Gramsci (2001), Acácia Kuenzer (2010) and others. In this way we emphasize the importance of teacher training, this training, which is intrinsically directed to the world of work, towards an omnilateral education. In order to do so, we find that in the course of the research, the international organizations interfere in the elaboration of educational policies, implying in the teacher training at the middle level a market character and that, therefore, this formation does not correspond to an integral formation of the man.